MOTHERS MIDWIFERY NURSING MOTHERS IN MRS. N AGE 40 YEARS WITH HIGH RISK IN PMB BIDAN MARWATI, SKM, M.KES CILEGON CITY - BANTEN IN 2019 - Lina Marliana; Sulawati (Poltekkes 'Aisyiyah Banten, 2019)
High risk factors affecting labor are mothers aged <20 years or mothers> 35 years old, children> 4, birth distance less than two years, history of hereditary diseases. Based on the results of the 2014 Ministry of Health, women with high risk recorded 34%. While in Banten Province 2010 it was 38% and in 2018 in the city of Cilegon it was recorded 94%. In 2018 high-risk delivery mothers in Marwati PMB were 19%, and in 2019 from January to March 10%. The purpose of this case study is to be able to provide midwifery care for high-risk maternity mothers. The case study research method is a qualitative case study, because it is conducted by interview and observation. Primary and secondary data types from interviews, history taking, direct observation. Maternity care for mothers in Ny. N with high risk, there is bleeding due to weak contractions and the presence of blood clots carried out in massase and exploration. It is recommended for all women to have an examination as early as possible to prevent complications at the time of delivery